Assessing Genetic Variability in Wheat (Triticum aestivum L.) Under Timely and Late Sown Conditions for Tolerance Towards Terminal Heat Stress - Karla, Uttej; Choudhary, Vinay Kumar; Singh, Satish Kumar; Vignesh, S.; Ellandula, Anvesh (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at wheat experimental farm, Post Graduate College of Agriculture, DRPCAU, Pusa, Bihar to quantify the genetic variability among twenty-nine wheat genotypes under timely and late sowing conditions for tolerance towards terminal heat stress during rabi 2020–2021. The trial was performed in three replications using Randomized Block Design. The study included estimates of genetic variability parameters such as mean, range, phenotypic coefficient of variability, genotypic coefficient of variability, broad-sense heritability, and genetic advance over % of mean. The ANOVA estimations showed that there’s considerable variation across genotypes for all twelve traits investigated across both environments. Traits like grains spike-1 and harvest index displayed considerable genotypic and phenotypic variances across both environments indicating the relevance of these traits in stress conditions. Tillers plant-1 and grain yield plant-1 displayed high genotypic and phenotypic coefficient of variation in timely and late conditions respectively. High heritability reported for traits like days to 50% flowering, canopy temperature, harvest index, grain yield plant-1, tillers plant-1, thousand grain weight and grains spike-1 in both conditions. Under both conditions, tillers plant-1, grains spike-1, harvest index and grain yield plant-1 reported strong heritability along with high genetic advance over % of mean. As a result, direct selection may be made using these features for further genotype improvement under stress conditions for improved heat tolerance.